Fatigue pada Anak dengan Diabetes Melitus Tipe 1 - Putri Melisa Duha; Nur Agustini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify fatigue that occurs in the age group of children with Diabetes Mellitus (DM) type 1 systematically. The method used is a systematic review by searching electronic database literature through EBSCOhost, Sage Publication, Science Direct, and Google Scholar by examining research results from published articles. The results showed that two of the existing pieces looked at sleep disturbances as a contributing factor to fatigue, and two reports stated that hypoglycemia symptoms were associated with the incidence of fatigue. Two articles investigated the lifestyle of children with type 1 DM as a factor causing fatigue, and one looked at anxiety as a factor. Factors causing fatigue. In conclusion, fatigue in children with type 1 diabetes can be related to various factors such as sleep disturbances, symptoms of hypoglycemia, lifestyle, and anxiety. Keywords: Children, Type 1 Diabetes Mellitus, Fatigue, Fatigue